2003
DOI: 10.1143/jjap.42.1
|View full text |Cite
|
Sign up to set email alerts
|

Base-Metal Electrode-Multilayer Ceramic Capacitors: Past, Present and Future Perspectives

Abstract: Multilayer ceramic capacitor (MLCC) production and sales figures are the highest among fine-ceramic products developed in the past 30 years. The total worldwide production and sales reached 550 billion pieces and 6 billion dollars, respectively in 2000. In the course of progress, the development of base-metal electrode (BME) technology played an important role in expanding the application area. In this review, the recent progress in MLCCs with BME nickel (Ni) electrodes is reviewed from the viewpoint of nonred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
644
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,044 publications
(687 citation statements)
references
References 50 publications
2
644
1
4
Order By: Relevance
“…Barium titanate (BaTiO3) is a perovskite type (ABO3) ferroelectric material [1] employed as main component in a variety of environmentall-friendly electronic devices such as memory storage systems, piezoelectric transducers, pyroelectric detectors and multi-layer ceramic capacitors [2][3][4][5]. However, in order to meet the technological requirements that these devices must satisfy, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Barium titanate (BaTiO3) is a perovskite type (ABO3) ferroelectric material [1] employed as main component in a variety of environmentall-friendly electronic devices such as memory storage systems, piezoelectric transducers, pyroelectric detectors and multi-layer ceramic capacitors [2][3][4][5]. However, in order to meet the technological requirements that these devices must satisfy, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, metal/ceramic multilayers have also been found as optically absorbing coatings in solar collectors for thermo-solar energy generation [8][9][10]. Finally, the development of cellular phones has pushed the research on base-metal electrode multilayer ceramic capacitors because of their high capacitance at large frequencies [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Barium titanate (BT) and strontium titanate (ST) are the most popular perovskite oxides for electronic device application such as multilayered ceramic capacitor (MLCC), positive temperature coefficient (PTC) thermistor, and so on. 6 The bulk BT has ferroelectricity at room temperature; in contrast, ST is a paraelectric material. It has been reported that BT/ST artificial superlattice thin film which consists of a few unit cells per layer has ferroelectricity and enhanced dielectric properties.…”
mentioning
confidence: 99%